Behavior Individuality: A Focus on Drosophila melanogaster - Mollá-Albaladejo, Rubén; Sánchez-Alcañiz, Juan A. (Frontiers in Physiology, 2021)
Among-individual behavioral differences results from the well known interplay of nature and nurture. Minute differences in the genetic code, can lead to differential gene expression and function, having dramatic effects both during developmental processes and adult behavior. Environmental factors, epigenetic modifications and also gene expression and function are the responsible for the generation of stochastic behaviors. The advent of high-throughput sequencing in the last decade has facilitated the study of the genetic basis of behavior and individuality, as we can now study the genomes of multiple individuals and infer which genetic variations might be responsible for the observed behavior. In addition, the development of high-throughput behavioral paradigms, where multiple isogenic animals can be observed and analyzed in various environmental conditions, has again facilitated the study of the influence of genetic and environmental variations in animal personality. Particularly, Drosophila melangoaster has been the focus of a great effort to understand how inter individual behavioral differences emerge, as the possibility to use large numbers of animals, the quantity of isogenic populations and even more the possibility to modify neuronal function, has made it an ideal model where to search for the origins of individuality. In the present review we will focus on the recent findings that try to shed light onto the emergence of individuality with a particular interest in Drosophila melanogaster.